Ravīndranāthaṭāgūr eḻutiya jīvitasmrtikaḷ : Baṅgāḷigranthattinṯe vivarttanaṃ - Tagore, Rabindranath, 1861-1941 (SAMP early 20th-century Indian books project, 1947)
Autobiography of Rabindranath Tagore, 1861-1941.